Determinantes de la duración del desempleo en áera metropolitana de cali 1988-1998 - Castellar, Carlos; Uribe, José Ignacio (Sociedad y Economía, 2006)
An econometric model was elaborated and was tested with data for the Metropolitan Area of Cali, 1988-1998. In agreement with this model, the determinants of unemployment duration are the following: home position, gender, non-labor income, educative level, experience and the wage coefficient of variation. The model isolates a component of macroeconomic nature that moves along the same trajectory of average duration. This result permits to infer that labor unemployment duration evolves anticyclically.